RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND SLEEP QUALITY WITH MUSCLE MASS IN FEMALE MEDICAL STUDENTS - Kevina Nuraini Yusuf; Nurfitri Bustamam; Tri Faranita; Diana Agustini Purwaningastuti (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2024)
Female medical students tend to have low physical activity (PALP levels accompanied by poor sleep quality. This condition could disrupt muscle protein metabolism, resulting in decreased muscle mass at a young age. This study aims to determine the association between physical activity and sleep quality with muscle mass in female medical students. A cross-sectional study design was conducted on 60 female students according to the criteria selected using stratified random sampling. The study instruments were Tanita Medical Body Composition Analyzer (MC-980MA Plus), Global Physical Activity Questionnaire (GPAQ), and Pittsburgh Sleep Quality Index (PSQI). Study results found that 34 (56,7%) subjects, 23 (38,3%) subjects, and 3 (5%) subjects had low, normal, and high muscle mass respectively.  Physical activity levels PAL of 25 (41,7%) subjects were low, 30 (50%) subjects were moderate, and 5 (8,3%) subjects were high. A number of 55 (88,3%) subjects had poor sleep quality, while the other 7 (11,7%) subjects had good sleep quality. Multiple regression logistic test showed that PAL had more effect on muscle mass (p = 0,000; OR = 14,056, CI = 3,488-56,637) compared to sleep quality (p = 0,104; OR = 7,680, CI = 0,657-89,726). Therefore, young adults need to exercise regularly and perform sleep hygiene to maintain their muscle mass.